Ignatius MacFarland : frequency freak-out! - Feig, Paul (Little, Brown, 2010)
Twelve-year-old Iggy and his friend Karen find themselves transported to an alternate reality, where the trees that rule a vast underground city are convinced that Iggy and Karen are in league with the human that stole their gold.